Natural mortality of noctuid larvae (Lepidoptera) in the Ecuadorian Andes: a first approximation - BENZING, ALBRECHT; KLEESPIES, REGINA G.; PONCE, FERNANDO (Revista Colombiana de Entomología, 2000)
In the Central Andes of Ecuador, 857 larvae of Noctuidae (Lepidoptera) were collected on maize and different vegetable crops to study the rate and factors of natural mortality. Larvae belonged to eight species, Agrotis deprivata and A. ipsilon being the most important. Total mortality caused by defined natural enemies reached 35 %, with Incamyia sp., Linnaemyia sp.; Prosopochaeta sp. (Díptera: Tuchinidae), Cotesia spp., Meteorus sp. (Hymenoptera: Braconidae), two isolates of microsporidia and nuclear polyhedrosis virus (NPV) as major factors. Another species of Meteorus, a granulosis virus and a fungus of the order Entomophthorales were of minor importance. Ali parasitoids and entomopathogens are new records for the Ecuadorian highland. The need for more systematic research on potential agents for biological control of Noctuidae is discussed.